Development of Australian physical activity and screen time guidelines for outside school hours care: an international Delphi study - Rosa Virgara; Anna Phillips; Lucy Lewis; Mandy Richardson; Carol Maher (BMC, 2021)
Abstract Background Children's activity patterns in the periods before and after school make a key contribution to achieving 24-h movement guidelines. There are currently no national-level guidelines informing physical activity and screen time practices in Outside School Hours Care (OSHC) programs anywhere in the world. This study aimed to work with industry, government and academic stakeholders to develop draft physical activity and screen time guidelines for use in Australian OSHC. Methods A 4-round online Delphi survey was conducted from May 2019 to January 2020. The Delphi participants included national and international experts and stakeholders from academia, education, government, health and the OSHC sectors. Round 1 consisted of open-ended questions exploring physical activity, screen time and sedentary behaviour in various periods of OSHC (before school, after school and vacation care). In rounds 2 and 3, participants rated the importance of items generated from the first round for inclusion in national guidelines using a Likert scale (1-9). Consensus was defined a priori as ≥80% of respondents rating an item as "critically important" (score 7-9). Between rounds 3 and 4, the guideline development panel used the consensus items, systematic review evidence, and followed the GRADE process, to draft the guidelines. In round 4, participants were invited to provide feedback on the draft guidelines and comment on barriers and enablers to implementation. Results Sixty-seven stakeholders agreed to participate, with response rates 61, 81, 54 and 72% for the four rounds respectively. Of the 123 items generated across the three rounds, 48 statements achieved consensus agreement as critically important for inclusion in the guidelines. These included offering a variety of physical activities (free play, playground and equipment) and restriction of screen time. The final round provided feedback on the draft guidelines. The wording of the guidelines was found to be appropriate and preliminary enablers and barriers to implementation were identified. Conclusions This world-first expert and stakeholder consultation has underpinned the development of the draft Australian guidelines for physical activity and screen time in OSHC. Ongoing work is needed to further refine the guidelines, determine current rates of compliance with the guidelines and implement the guidelines into practice.